Faktor Penyebab Perilaku Agresi Verbal Siswa SMK Swasta di Kota Semarang - Nurjanah, Alif; Suharso, Suharso (Konseling Edukasi : Journal of Guidance and Counseling, 2023)
Factors Causing Verbal Aggressive Behavior of Private Vocational School Students in Semarang City. Verbal aggression behavior’s students does’nt appear by itself, this study aims to determine the factors cause verbal aggression behavior of students of vocational high school. Verbal aggressive behavior’s students, concerns the BK teacher or School Counselor as an agent helping students develop in positive and optimal direction. This research uses a quantitative approach with a descriptive survey type research method. Total population of 7746 respondents. The sampling technique used was cluster random sampling, simple random sampling with a sample of 334 respondents from 3 schools. Data collection using a questionnaire and psychological scale and data analysis techniques using descriptive analysis percentage. The results prove verbal aggression is in moderate category. The most factor causing verbal aggression is personal factor that is self adjustment and social factor is media influence. The low factor that causes verbal aggression behavior from social factors is frustration while personal factors is the factor of self-awareness.Keywords: Factors, Verbal Aggression, Student